A class of discrete distributions arising from difference of two random variables - Ong, S. H.; Shimizu, K.; Ng, C. M. (Elsevier, 2008)
This paper considers a class of distributions arising from the difference of two discrete random variables belonging to the Panjer family of distributions. Some distributional properties and computation of probabilities are discussed. Goodness of fit and tests of hypotheses involving the likelihood ratio, score and Wald tests have been considered. As an illustration, an application to paired count data is given